Influence of Decentralization and Type of Patient on Loss to Follow-up among Multidrug-Resistant Tuberculosis Patients in Indonesia from 2014 to 2015 - Noerfitri, Noerfitri; Sutiawan, R.; Wahyono, Tri Yunis Miko; Hartono, Pratiwi Ayuningtyas (UI Scholars Hub, 2019)
Drug-resistant tuberculosis (TB) patients have a greater risk of loss to follow-up (LTFU) than drug-sensitive TB patients, due to their longer treatment duration. This study aimed to determine the influence of decentralization and patient type on LTFU among multidrug-resistant TB (MDR-TB) patients in Indonesia. A retrospective cohort study was conducted at all MDR-TB treatment healthcare facilities in Indonesia from 014 to 2015. Using total sampling technique, 961 patients were examined and sampled. Of these patients, 86.03% were decentralized. Patients were classified into types as follows: 35.17% were “relapse” patients, 5.52% were “new,” 13.94% were classified as “after LTFU” patients, 23.10% were “treatment failure category 1” patients, 20.29% were “treatment failure category 2” patients, and 1.90% were classified as “other types” patients. Decentralization reduced LTFU risk by up to 46% (HR = 0.54, 95% CI 0.35–0.84). LFTU in “after LTFU,” “treatment failure category 2,” and “other types” patients was higher by 50%, 53%, 74%, respectively compared to LFTU occurrence in “relapse” (baseline) patients. Among “treatment failure category 2 patients, female patients were 2.13 times more likely to have an occurrence of LFTU, while male patients were 0.55 times as likely to have an occurrence of LFTU, compared to “relapse” type patients of the same sex.